Marine mammal occurrence in deep waters of the Brazil-Malvinas confluence off Argentina during summer - Mandiola, María Agustina; Giardino, Gisela Vanina; Bastida, Julian; Rodriguez, Diego Horacio; Bastida, Ricardo Oscar
This article presents the results of marine mammal occurrence at the Brazil-Malvinas Confluence in the Argentine Sea shelf break during a summer survey. A total of 61 marine mammal sightings were recorded. The most frequent species recorded were South American fur seals (Arctocephalus australis; 75.4%; 78-4670m), followed by sperm whales (Physeter macrocephalus; 8.2%; 478-2825m), sei whales (Balaenoptera borealis; 4.9%; 1513-4674m) and long-finned pilot whales (Globicephala melas; 3.3%; 1119-1534m), with a small number of unidentified cetaceans (4.9%; 87-2248m). This new information about marine mammal species in the Brazil-Malvinas Confluence updates knowledge of their distribution in this highly productive area. Este artigo apresenta os resultados de registros de mamíferos marinhos obtidos durante um embarque na região sob influência da zona de Convergência Brasil-Malvinas na quebra da plataforma do Mar Argentino durante o verão austral. Foi obtido um total de 61 avistamentos. As espécies mais comuns foi lobo-marinho-sul-americano (Arctocephalus australis, 75.4%; 78-4670m), cachalote (Physeter macrocephalus, 8.2%; 478-2825m), baleia-sei (Balaenoptera borealis; 4.9%; 1513-4674m) e baleia-piloto (Globicephala melas, 3.3%; 1119-1534m). A presente informação contribui para uma melhor compreensão sobre a ocorrência de mamíferos marinhos em uma área altamente produtiva que é a Convergência Brasil-Malvinas. Fil: Mandiola, María Agustina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencia Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Giardino, Gisela Vanina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencia Exactas y Naturales. ...